Optimizing locked nucleic acid/2′-O-methyl-RNA fluorescence in situ hybridization (LNA/2′OMe-FISH) procedure for bacterial detection - Andreia S. Azevedo (2019)
Despite the successful application of LNA/2'OMe-FISH procedures for bacteria detection, there is a lack of knowledge on the properties that affect hybridization. Such information is crucial for the rational design of protocols. Hence, this work aimed to evaluate the effect of three essential factors on the LNA/2'OMe hybridization step-hybridization temperature, NaCl concentration and type and concentration of denaturant (formamide, ethylene carbonate and urea). This optimization was performed for 3 Gram-negative bacteria (Escherichia coli, Pseudomonas aeruginosa and Citrobacter freundii) and 2 Gram-positive bacteria (Enterococcus faecalis and Staphylococcus epidermidis), employing the response surface methodology and a Eubacteria probe. In general, it was observed that a high NaCl concentration is beneficial (from 2 M to 5 M), regardless of the denaturant used. Urea, formamide and ethylene carbonate are suitable denaturants for LNA/2'OMe-FISH applications; but urea provides higher fluorescence intensities among the different bacteria, especially for gram-positive bacteria and for P. aeruginosa. However, a unique optimal protocol was not found for all tested bacteria. Despite this, the results indicate that a hybridization solution with 2 M of urea and 4 M of NaCl would be a proper starting point. Furthermore, a hybridization temperature around 62 degrees C, for 14 bp probes with LNA monomers at every third position of 2'OMe and 64% of GC content, should be use in initial optimization of new LNA/2'OMe-FISH protocols.